Exopolysaccharide, Isolated From a Novel Strain Bifidobacterium breve lw01 Possess an Anticancer Effect on Head and Neck Cancer – Genetic and Biochemical Evidences - Wang, Lin; Wang, Yifei; Li, Qingxiang; Tian, Kaiyue; Xu, Le; Liu, Guorong; Guo, Chuanbin (Frontiers in Microbiology, 2019)
Exopolysaccharide (EPS) from probiotic bacteria received more attention these days for its bioactivities on immune system modulation, intestinal microbiota modulation, antioxidants and anticarciogenic effect. Yet, these bioactivities are of interspecies diversity, thus examining the gene clusters of EPS and biosynthesis pathways is essential for selecting the better application of specific EPS. In this study, we isolated a new Bifidobacterium strain, named B.breve lw01. A complete genome of B.breve lw01 was sequenced revealing a circular 2,313,172 bp chromosome. Furthermore, a deep excavation of genome sequence by different database based on the comparison-selected results was performed to explore the gene cluster responsible for EPS synthesis. We found that B. breve lw01 harbors a new EPS-encoding cluster with 19 predicted genes, which could be divided into three groups according to its hypothesis biosynthesis pathway. By tertiary purification, high purity EPS could be obtained. For the bioactivity, these EPS showed to possess anticancer activity against Head and Neck Squamous Cell Carcinoma cell line and the preliminary mechanisms could rely on its cell cycle arrest and effect of cell apoptosis promotion. To conclude, this study examined the biosynthesis and bioactivity of a new isolated Bifidobacterium-EPS, which could be used to clarify its further application in functional food or drug industry.